Ectoparasite infestation and Vibrio alginolyticus bacterial infection in super-intensive ponds with high ammonia levels of Penaeus vannamei - Deriyanti Aprillia (EDP Sciences, 2021)
Disruption to fish and shrimp farming can be caused by poor water quality or invading pathogens. This study aims to determine the degree of ectoparasite infestation and Vibrio alginolyticus bacterial infection in super-intensive ponds. This study uses a survey method. Water and shrimp sampling was carried out at three stations and two sampling points. The study was conducted from January until February 2020. Water quality, parasite, and bacterial identification were measured at the Jepara Center for Brackish Water Cultivation Fisheries. This study showed that all samples were positively infested with Zoothamnium, Epistylis, and Vorticella parasites. The highest number of Vibrio bacteria was found at an average of 1.16 x 105 cells / mL. Based on Pearson correlation analysis, the relationship between the total number of bacteria and the ectoparasite intensity level in Pacific white shrimp has a value of 0.015 with an R-value = 0.828. This indicates that the presence of high ectoparasite intensity. Water quality data also shows a very close relationship between the level of ectoparasite intensity and the stocking density of vannamei shrimp.